El Perú actual y su (in)dependencia de lo que sucede en el contexto internacional. Entrevista a Pedro Pablo Kuczynski Godard - Trazegnies Granda, Fernando de (2013)
Peru's reality should be analyzed carefully inorder to understand the situation in which most Peruvians actually are. It is of particular relevance to understand the role that the State and the tax system developed in it have in the country’s economy. A well known Peruvian economist analyzes Peru’s economic situation through the comparison benchmark countries that are somehow very influent on us. It is through a deep approach that the interviewee schemes the main issues of our country and enables to make proposals based on its reality, as well  as to make some projections about the country’s future.